2014
DOI: 10.1002/aoc.3186
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II) complexes bearing di‐ and monochelate fluorinated β‐ketonaphthyliminato ligand and their catalytic properties towards vinyl‐addition polymerization and copolymerization of norbornene and ester‐functionalized norbornene derivative

Abstract: Fluorinated β-ketonaphthyliminate ligand CF 3 C(O)CHC[HN(naphthyl)]CH 3 (L1) and Pd(II) complexes with dichelate fluorinated β-ketonaphthyliminato ligand, {CF 3 C(O)CHC[N(naphthyl)]CH 3 } 2 Pd (C1), as well as with monochelate fluorinated β-ketonaphthyliminato ligand, {CF 3 C(O)CHC[N(naphthyl)]CH 3 }Pd(CH 3 )(PPh 3 ) (C2), were synthesized and their solid-state structures were confirmed using X-ray crystallographic analysis. The Pd(II) complexes were employed as precursors to catalyze norbornene (NB) homo-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…A large discrepancy was found between the experimental and theoretical values of the molecular weights, suggesting a poorly controlled polymerization process, with the PDI (PDI = M w / M n ) values ranging from 1.5–3.6. A similar wide distribution of PDI values is observed in the literature for the polymerization of norbornenes by group 10 metals , , , , , . The polymerization activity for palladium complexes toward norbornene is largely dependent on the coordination environment around the metal center and the substituents on the monomer and can vary greatly from just a few numbers to several millions , , , .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…A large discrepancy was found between the experimental and theoretical values of the molecular weights, suggesting a poorly controlled polymerization process, with the PDI (PDI = M w / M n ) values ranging from 1.5–3.6. A similar wide distribution of PDI values is observed in the literature for the polymerization of norbornenes by group 10 metals , , , , , . The polymerization activity for palladium complexes toward norbornene is largely dependent on the coordination environment around the metal center and the substituents on the monomer and can vary greatly from just a few numbers to several millions , , , .…”
Section: Resultssupporting
confidence: 85%
“…Amongst transition metal catalysts, palladium‐based systems are highly active toward norbornene polymerization and produce high molecular weight vinyl polynorbornenes , . Most palladium catalysts feature bidentate or monodentate supporting ligands since an open coordination sphere is necessary for monomer coordination , , , . Commonly employed systems also require the use of strong Lewis acids/alkylating reagents (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The ester group itself helps to improve the compatibility of polyolefins. , In addition, this group can be altered to other chemical functionalities by participating in post-polymerization modification, such as hydrolysis, , transesterification, and amidation. , Therefore, a COC functionalized with ester groups is expected to have a role as a versatile platform that can be transformed to functional materials suitable for desired applications. Late transition metal complexes with low oxophilicity, mostly Ni­(II) and Pd­(II) complexes, have been used as catalysts for the vinyl addition copolymerization of NB and polar monomer with ester functionality and have shown promising catalytic performance. Several previous studies have confirmed that Ni­(II) catalysts achieve higher catalytic activity than Pd­(II) catalysts. ,, Numerous ligands have been investigated for Ni­(II)-based catalyst systems. In particular, Ni­(II) complexes bearing N,O-chelating β-ketoimine ligands that form bis­(β-ketoimino)­nickel­(II) complexes have been reported to exhibit moderate catalytic activity. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, analysis of 2 by single crystal X-ray diffraction studies clearly display the square planar configuration with a typical trans-bis-κ 2 -N,O ligand donor set (τ 4 = 0.00). [14][15][16][17][18][19][20][21][22][23][24] In this Note, we re-examined the synthesis and properties of 2 using a combination of Density Functional Theory (DFT) and spectroscopic techniques (IR, UV-Vis., NMR, etc.). This work demonstrates that the title complex is, in fact, diamagnetic and hence NMR spectra ( 1 H, 13 C, 19 F) of the compound can be measured.…”
Section: Introductionmentioning
confidence: 99%